A systematic review and meta-analysis of randomized placebo-controlled trials of DHEA supplementation of bone mineral density in healthy adults. (2nd November 2019) - Lin, Han; Li, Lei; Wang, Qi; Wang, Yun; Wang, Jiamin; Long, Xiaolin
Abstract: To find out if DHEA replacement improves bone mineral density (BMD) in healthy older adults. We systematically searched Medline via PubMed, Embase, and the Cochrane Library Center Register to identify randomized controlled trials up to October 2018. Effect estimates were performed in random effect models. Bone mineral density of hip and trochanter, total body, lumbar spine, and femoral neck were conducted. Hip BMD increased significantly above placebo group in women who took DHEA supplementation (SMD –0.5[–0.95, –0.04], p  = .03). The SMD of trochanter BMD of women in placebo group than DHEA group was –0.55 [–1.10, 0.00], p  = .05. Insulin-like growth factor 1 (IGF-1) did not change in men compared to placebo group also (–0.56 [–1.22, 0.10], p  = .09). In women, IGF-1 significantly improved in DHEA supplementation group than placebo group (–2.61 [–4.85, –0.38], p  = .02). In summary, the results of this meta-analysis suggest that DHEA replacement therapy can partially increase BMD of hip and trochanter in women. Similar results were not observed in men. More trials may be necessary to allow for a positive and clinically significant effect of DHEA on BMD.